The Changes of CTX, DPD, Osteocalcin, and Bone Mineral Density During the Postmenopausal Period - Park, Seok Gyo; Jeong, Seong Uk; Lee, Jae Hyun; Ryu, Sang Hyeong; Jeong, Ho Joong; Sim, Young Joo; Kim, Dong Kyu; Kim, Ghi Chan (Annals of rehabilitation medicine, 2018)
To investigate appropriate treatment time and useful bone turnover markers (BTMs) for monitoring bone turnover during the postmenopausal period, we analyzed changes of two bone resorption markers; serum carboxyterminal telopeptide of collagen I (s-CTX), urine deoxypyridinoline (u-DPD), one bone formation marker; serum osteocalcin (s-OC), and bone mineral density (BMD) in Korean postmenopausal women. Seventy-eight menopausal women were divided into three groups according to postmenopausal period: group I (0-5 years), group II (6-10 years), group III (≥10 years). All groups were subdivided into an osteoporosis group (T-score≤-2.5) and a non-osteoporosis group (T-score>-2.5). BTMs such as s-CTX, u-DPD, s-OC, and BMD (g/cm ) were measured by dual-energy X-ray absorptiometry (DXA) in all patients. Analysis of variables among groups based on the postmenopausal period was performed using ANOVA. There was significant negative correlation between BMD and postmenopausal period. The levels of all BTMs including s-CTX, u-DPD, and s-OC were highest in group II and the increased levels of all BTMs subsequently declined in group III. The levels of BTMs were higher in the osteoporosis groups than in the non-osteoporosis groups in all subjects. It was statistically significant that the level of s-CTX in group I was higher in the osteoporosis group than in the non-osteoporosis group. This study showed that bone resorption and bone formation were the highest 5-10 years after menopause, and s-CTX is more useful than u-DPD among the bone resorption markers. It's important to measure serially both BMD and BTM within 10 years after menopause for accurate diagnosis and management for postmenopausal osteoporosis.